Biologia da polinização e eficácia de polinizadores em Solanum melongena L. (Solanaceae) - Zambon, Vivian (2015)
The pollination is am essential environmental service to the development of various plant species, contributing to the provision of basic human food. Some species, like much of the genus Solanum, may present different floral morphs, which in turn can influence its reproduction. In this context, this study aimed to study the biology of pollination of Solanum melongena L. (Solanaceae). The specific objectives were: 1) to analyze the biology and floral morphology of the species; 2) verify the reproductive and sexual system of the species; and 3) to verify the wealth and the behavior of your floral visitors. The study was conducted in two areas of conventional agricultural crop in Estiva Gerbi and Piracicaba, both in the state of São Paulo. The floral visitors were observed between February and June 2014. The data of floral morphometry were collected with the aid of manual caliper and the differences between the measures were tested using the t test. The estimation of pollen production was given by counting the number of grains produced by anther. The number of viable pollen grains was quantified by cytoplasmic staining, with the technique of acetic carmine. To investigate the relationship between the frequency of pollinators and the availability of pollen, we calculated the Pearson correlation coefficient (r). To check the effectiveness of different pollinators in the formation of fruits and seeds of eggplant, we selected two species of bees with different foraging behaviors: Apis mellifera, which does not vibrate and Exomalopsis diminuta, which vibrates the flower anthers to release pollen. Variance analyses were performed to detect significant differences between fruits developed by both species. The reproductive system was analyzed by the formation of pollen tubes at different times after pollination different treatments are performed. Through the morphometric analysis, there was significant difference between the floral and reproductive structures of different morphs, featuring a polymorphism condition in style size to S. melongena. The observations found the presence of the bee genera Bombus, Xylocopa, Apis, Trigona, Pseudaugochloropsis, Oxaea and Exomalopsis. Concerning the behavior of each species, there has been a change both in relation to the form of collecting pollen on the flower in the length of stay. Concerning the reproductive system, it was noted formation of pollen tubes along the style and the same coming to ovule only in long style flowers, which may indicate a andromonoecious condition for the species under study. It is concluded for S. melongena that the action of pollinators is of great importance for its development, since even being self-compatible, the spontaneous self not proved to be sufficient for effective fertilization of their ovules. There are several species that play role of pollinators, but species with the vibration behavior contribute more effectively to the development of this culture.